Autonomous action and cooperativity between the ONECUT2 transcription factor and its 3′ untranslated region - Steadman, Kenneth; You, Sungyong; Srinivas, Dustin V.; Mouakkad, Lila; Yan, Yiwu; Kim, Minhyung; Venugopal, Smrruthi V.; Tanaka, Hisashi; Freeman, Michael R. (Frontiers in Cell and Developmental Biology, 2023)
The transcription factor ONECUT2 (OC2) is a master transcriptional regulator operating in metastatic castration-resistant prostate cancer that suppresses androgen receptor activity and promotes neural differentiation and tumor cell survival. OC2 mRNA possesses an unusually long (14,575 nt), evolutionarily conserved 3′ untranslated region (3′ UTR) with many microRNA binding sites, including up to 26 miR-9 sites. This is notable because miR-9 targets many of the same genes regulated by the OC2 protein. Paradoxically, OC2 expression is high in tissues with high miR-9 expression. The length and complex secondary structure of OC2 mRNA suggests that it is a potent master competing endogenous RNA (ceRNA) capable of sequestering miRNAs. Here, we describe a novel role for OC2 3′ UTR in lethal prostate cancer consistent with a function as a ceRNA. A plausible ceRNA network in OC2-driven tumors was constructed computationally and then confirmed in prostate cancer cell lines. Genes regulated by OC2 3′ UTR exhibited high overlap (up to 45%) with genes driven by the overexpression of the OC2 protein in the absence of 3′ UTR, indicating a cooperative functional relationship between the OC2 protein and its 3′ UTR. These overlapping networks suggest an evolutionarily conserved mechanism to reinforce OC2 transcription by protection of OC2-regulated mRNAs from miRNA suppression. Both the protein and 3′ UTR showed increased polycomb-repressive complex activity. The expression of OC2 3′ UTR mRNA alone (without protein) dramatically increased the metastatic potential by in vitro assays. Additionally, OC2 3′ UTR increased the expression of Aldo-Keto reductase and UDP-glucuronyl transferase family genes responsible for altering the androgen synthesis pathway. ONECUT2 represents the first-described dual-modality transcript that operates as both a key transcription factor driving castration-resistant prostate cancer and a master ceRNA that promotes and protects the same transcriptional network.